The Effect of Hydration Status on King-Devick Concussion Assessment and Symptoms Scores in Healthy Collegiate Athletes - Reineck, Jessica F.; Stiving, Lydia J.; Patterson, Andrea R; Fant, Katherine E.; Amundson, Jeremy T.; Turnquist, Tadd (My University, 2018)
To investigate the effects of hydration on concussion assessments including the King-Devick test and the Sport Concussion Assessment Tool 3 (SCAT3) symptom score. Twenty-eight Division III collegiate athletes (18-25 years of age) participated in this study. Each participant had two baseline King-Devick tests, a symptom score, and a urine specific gravity (USG) assessment. Participants then reported in a hydrated state (USG ≤ 1.021) and a hypohydrated state (USG ≥ 1.027) with at least 72 hours between each testing session. At the beginning of each testing session, participants completed a USG assessment to assure appropriate hydration parameters were reached. A King-Devick test and a symptom score were then completed. A paired-sample t-test indicated that King-Devick time was greater in a hypohydrated status as compared to a hydrated status, t(27) = 2.44, p = .022. There was also significant differences in symptom score and symptom severity in a hypohydrated state versus a hydrated state, t(27) = 2.97, p = .006 and t(27) = 2.41, p = .023). Hypohydration negatively affects symptom scores and King-Devick test time. When using the King-Devick test to assess concussion status, consideration of hydration status is needed.
Color poster with text, images, charts, and graphs.
Keywords: Hydration; Concussion; College athletes; Posters